Le mauvais usage de la démocratie en Côte d’Ivoire - Christian Bouquet (L'Espace Politique)
As all the other countries in the South, the Ivory Coast was invited to engage, in the early 90s, in a process meant to restructure its mode of governance to bring it closer to what countries in the North regard as a universal model : western-style democracy. At the same time, the Ivory Coast had to build a form of national identity within borders inherited from colonization. The task proved so arduous that it led to the country’s implosion. The analysis of the misunderstandings and incomprehensions, both actual and feigned, which surrounded the setting up of the democratic process in the Ivory Coast raises the issue of the relevance of the transplant and suggests a re-reading of precolonial history – including that derived from the oral tradition – in an attempt to understand the causes of the rejection by exploring other modes of human government while keeping our ethnocentrism at bay.